Some problems and features of a bank system of the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
The article analyzes theoretical and legal features influence of world crisis on a bank system and influence of a bank system of the country on economy and their main features and stages. Special attention is paid to consideration crisis situations, financial conditions of the country. During the writing of a scientific article, I view, read, studied, treated many scientific papers and used those that related to my theme of a scientific article. Ensuring the stability of the banking system of Kazakhstan is connected with the legal regulation of banking activities. In recent years, the banking system rose to the level of the developed world’s banking systems. In today’s transitional stage in the economy of the Republic of Kazakhstan, namely in the area of influence of the state on the banking mechanism increases the significance of theoretical and practical problems.Key words: Bank system, financial policy, legal regulation, ecocnomy, currency, crisi, bank, budget, national resource, bank relations, bank legislations.